Interspeech 2018 2018
DOI: 10.21437/interspeech.2018-1873
|View full text |Cite
|
Sign up to set email alerts
|

Prominence-based Evaluation of L2 Prosody

Abstract: Prosody in terms of word and sentence stress is one of the most difficult features for many second language (L2) speakers to learn and it can be hypothesized that assessing the learner's prosodic abilities could provide a good measure for assessing the learners' spoken language skills in general. Automatic assessment is, however, dependent on reliable automatic analyses of prosodic features for comparing the productions between native (L1) and L2 speech. Here we investigate, whether estimated prosodic prominen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
(12 reference statements)
1
3
0
Order By: Relevance
“…However, distinguishing between neighboring levels, especially at the higher end of the scale, proved more challenging. This was also the case in our previous studies using the same CEFR scale ( Kallio et al, 2017 , 2018 , 2020 ). We suspect one reason for this to be the cumulative nature of the rating scale: the differences between proficiency levels are greater at the lower part of the scale because the language learning process is seen as progressive or accumulative.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…However, distinguishing between neighboring levels, especially at the higher end of the scale, proved more challenging. This was also the case in our previous studies using the same CEFR scale ( Kallio et al, 2017 , 2018 , 2020 ). We suspect one reason for this to be the cumulative nature of the rating scale: the differences between proficiency levels are greater at the lower part of the scale because the language learning process is seen as progressive or accumulative.…”
Section: Discussionsupporting
confidence: 86%
“…This allows us to take into account both word and sentence level production of prominence and compare the stress realizations between speakers in more detail. In Kallio et al (2018Kallio et al ( , 2020, we compared the estimated syllable prominence values between L2 and native speakers of Finland Swedish from read utterances and found that the higher the correlation in prominence values between native and L2 speakers, the better the prosodic proficiency grades of L2 speakers. However, the previous studies provided somewhat unexpected results regarding the feature combinations that best predicted the proficiency scores: energy and duration together provided the best results, which indicate that in the speech of L2 learners there might be a revealing pattern in the use of these features when producing prominence.…”
Section: Syllable Prominencementioning
confidence: 99%
See 2 more Smart Citations